Contending legitimacy in world politics the state, civil society and the international sphere in the twenty-first century - Winter, Bronwyn; Sorbera, Lucia (Routledge, Taylor & Francis Group, 2018)
Legitimacy, along with security and democracy, is arguably one of the most widely used global buzzwords of the new millennium. This book problematizes this notion, from various contextual standpoints, disciplinary and theoretical perspectives. Taking a comparative, transnational and bottom-up approach to the study of political legitimacy, this book sheds light on multiple perceptions by different actors (institutions, civil society, majoritarian and minority subjects), analysing the notion of political legitimacy from a critical perspective.